PENGARUH KECERDASAN EMOSIONAL DAN KARAKTERISTIK INDIVIDU TERHADAP MINAT BERWIRAUSAHA MAHASISWA MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS TADULAKO - Muhammad Hasby; Idris Azis; Andi Indriani (Universitas Tadulako, 2015)
The aim of this research is to determine simultaneous and partial influence of emotional intelligence (X1) and individual characteristics (X2) on entrepreneurship interests (Y). Subject of the research is students of Management Faculty of Economics, Tadulako University of 88 students, which consists of 28 students of 2012 batch, 26 students of 2013 batch, and 34 students of 2014 batch. Data collection methods applied are observation, interviews, and questionnaires; data analysis is multiple linear regressions with SPSS software for Windows Release 16.0. The result shows that: 1) emotional intelligence and individual characteristics simultaneously have significant influence on entrepreneurship interests of students in the Faculty of Economics, Tadulako University, 2) emotional intelligence has significant influence on entrepreneurship interests of students in the Faculty of Economics, Tadulako University, and 3) individual characteristics have significant influence on entrepreneurship interests of students in the Faculty of Economics, Tadulako University. Penelitian ini bertujuan untuk mengetahui pengaruh secara serempak dan parsial dari Kecerdasan Emosional (X1) dan Karakteristik Individu (X2), terhadap Minat Berwirausaha (Y). Subjek dalam penelitian ini adalah mahasiswa Manajemen Fakultas Ekonomi Universitas Tadulako, dengan sampel 88 orang, yang terdiri dari 28 mahasiswa manajemen angkatan 2012, 26 mahasiswa manajemen angkatan 2013 dan 34 mahasiswa manajemen angkatan 2014. Pengambilan data menggunakan metode observasi, wawancara, dan kuesioner kemudian diolah dengan menggunakan alat analisis regresi linear berganda dengan program SPSS For Windows Release 16.0. Hasil penelitian ini menunjukkan bahwa 1) Kecerdasan Emosional dan Karakteristik Individu secara serempak berpengaruh signifikan terhadap Minat Berwirausaha mahasiswa Manajemen Fakultas Ekonomi Universitas Tadulako, 2)Kecerdasan Emosional berpengaruh signifikan terhadap Minat Berwirausaha mahasiswa Manajemen Fakultas Ekonomi Universitas Tadulako, dan 3) Karakteristik Individu berpengaruh signifikan terhadap Minat Berwirausaha mahasiswa Manajemen Fakultas Ekonomi Universitas Tadulako.